Pengaruh Menggunakan Media Pembelajaran Pada Aplikasi Game Kahoot Terhadap Evaluasi Pembelajaran PAI di SMP Swasta An-Nizam Medan - Azmia, Irza; Mario Kasduri (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
This application is a game-based learning media that is able to create a lively and fun atmosphere in the classroom. By using the Kahoot application, learning becomes very fun and makes students not bored when following lessons that are difficult to understand.       Learning evaluation is a process used to determine the level of achievement of predetermined learning objectives through systematic activities. The Kahoot application is a web-based learning media or application that is used as an online-based evaluation process tool that makes it easier for teachers to increase students' interest in participating in evaluation activities. The aim of this research is to determine the process of using the Kahoot application as a digital-based game tool in the process of evaluating Islamic Religious Education learning at SMP Swasta An-Nizam in Medan.